Finite Element Analysis in Dentistry - Improving the Quality of Oral Health Care - Soares, Carlos José; Versluis, Antheunis; Valdivia, Andréa Dolores Correia Miranda; Bicalho, Aline Arêdes; Veríssimo, Crisnicaw; Barreto, Bruno de Castro Ferreira; Roscoe, Marina Guimarães (IntechOpen, 2012)
None